Mental health of parents of children and adolescents who require special health care - Eliana Roldão dos Santos Nonose; Rosane Meire Munhak da Silva; Eliane Tatsch Neves; Débora Falleiros de Mello; Adriana Zilly; Aline Cristiane Cavicchioli Okido; Regina Aparecida Garcia de Lima (Associação Brasileira de Enfermagem, 2024)
ABSTRACT Objective: To identify the manifestations presented by parents of children and adolescents who require special health attention that can impact their mental health. Methods: exploratory, qualitative research, based on the concept of vulnerability, with data collection carried out through interviews with 18 parents of children and adolescents with special health care needs, hospitalized in the pediatric ward of a hospital in Paraná, between May/2017 and May/ 2018. Data analyzed by inductive thematic analysis. Results: parents experienced situations of vulnerability when providing care at home, with repercussions on their mental health, expressed by manifestations of lack of protection, anxiety and depression. Final considerations: It is important that health professionals seek to expand actions to promote care and reduce situations that generate threats, insecurities, concerns and damage to the health of parents, which can impact and further weaken care for children and adolescents who need attention especially health.